School Engagement and Academic Resilience of High School Students in Klungkung Regency Bali - Zarinathi, Komang Merisa Naraswari; Huwae, Arthur (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
This study explores the correlation between school engagement and academic resilience among high school students in Klungkung Regency, Bali, using a quantitative approach with a correlational analysis design. 243 students from five high schools were selected via simple random sampling. Measures included the School Engagement Measure (SEM)-MacArthur (α = 0.851) and the Academic Resilience Scale-30 (ARS-30) (α = 0.884). Hypothesis testing revealed a Pearson correlation value of 0.615, with a significance level of 0.000 (p<0.01), These findings demonstrate that school engagement is a factor that significantly correlates with academic resilience among high school students in Klungkung Regency, Bali. Keywords: school engagement, academic resilience, high school students.